The Role of Islamic Education in Strengthening Social Religious Independence and Empowerment Community in Ngali Village - Amiruddin Amiruddin; Ruslan Ruslan; Ihlas Ihlas (CV. Creative Tugu Pena, 2025)
This study aims to examine in depth the role of Islamic education in strengthening communal independence and socio-religious empowerment of the community in Ngali Village, Belo District, Bima Regency, West Nusa Tenggara. This research is strengthened by the empirical gap between the transformative potential of Islamic education, especially through Islamic boarding schools (pesantren), madrasahs, majelis taklim (Islamic study groups), and community-based religious study groups (pesantren) with the reality of socio-economic dependency that is still rooted in rural Indonesian Muslim communities. This study uses a qualitative approach with an in-depth case study design that combines participant observation, in-depth interviews with 32 key informants, and analysis of institutional documents over twelve months. The research findings identify four transformative mechanisms: strengthening epistemic capacity based on Islamic values; the formation of religious social networks that expand social capital; internalization of Islamic work ethics as a basis for economic independence; and the construction of collective religious identity that strengthens social cohesion and community resilience. This research contributes to the development of a community-based Islamic education model that goes beyond ritual-normative orientation to a comprehensive social transformation agenda. The theoretical and practical implications of this research are relevant for the development of Islamic education policies in rural Indonesia and the context of the global Muslim community facing the challenges of modernization.